2013
DOI: 10.4236/ojmm.2013.34033
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility Pattern of Asymptomatic Urinary Tract Infections of Bacterial and Parasitic Origins among University Students in Redemption Camp, Ogun State, Nigeria

Abstract: Asymptomatic urinary tract infections (UTIs) of bacterial and parasitic origins occur in both males and females where bacteria and/or parasites are present in the urine, with the absence of clinical signs or symptoms in the host. Using microbiological methods, mid-stream urine collected from sixty (60) Redeemer's University students comprising apparently healthy 30 male and 30 female undergraduate students were examined. The samples were cultured on CLED and MacConkey agar. Bacteriuria was observed in 15 (25%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
12
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
(25 reference statements)
8
12
2
Order By: Relevance
“…E. coli, S. aureus, K. pneumoniae and S. faecalis also showed a resistance pattern >50% for most of drug used as first line of treatment. This is consistent with other study [9]. Ciprofloxacin and nalidixic acid revealed 85.7-100.0% and 73.6-100.0% activity range respectively.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…E. coli, S. aureus, K. pneumoniae and S. faecalis also showed a resistance pattern >50% for most of drug used as first line of treatment. This is consistent with other study [9]. Ciprofloxacin and nalidixic acid revealed 85.7-100.0% and 73.6-100.0% activity range respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Many studies reported the significance of UTI during pregnancy although pregnancy does not cause UTI [3][4][5][6], however, the complexity of urinary tract system and changes during pregnancy account for susceptibility to infection [3][4][5]7,8] Urinary tract infections have been reported in all age groups and can occur in both sexes [2,9] and pregnant women are not an exception [5,6]. UTI is a serious health problem worldwide affecting millions of people each year and the leading cause of Gram-negative bacteria [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E.coli showed resistant to all drugs used except Augumentin, Gentamycin and Vancomycin. This is consistent with other study (Ayoade, 2014). The average resistance of the isolates to all the antibiotics of gram positive cocci (Staphylococcus aureus) was higher than the gram negative bacilli (E.coli, Kl.pneumoniae and Pseudomonas auruginosae).…”
Section: Photo3:candida Albicans Photo4:aspergillus Nigersupporting
confidence: 82%
“…38 Study done by Ayoade et alfrom Nigeria, showed that all the isolates were resistant to Amoxycillin, Augumentin and Cotrimoxazole but most of the isolates were assessed to be highly susceptible to Ofloxacin. 39 Three antibiotics namely Ofloxacin, Gentamicin and Nitrofurantoin were found to be most effective for Gram negative bacteria while Gentamicin, Chloramphenicol and Cotrimoxazole were effective for Gram positive bacteria. A study by Amete Mihret Teshale et al from Ethiopia, Nitrofurantoin, Clindamycin and Ciprofloxacin were the most effective antibiotics for Gram positive isolates with less efficacy of Sulfamethoxazole/Trimethoprim for this bacteria.…”
Section: Gram Negative Isolatesmentioning
confidence: 95%